2011
DOI: 10.1007/s00259-011-1883-0
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of combined docetaxel and repeated high activity 186Re-HEDP in castration-resistant prostate cancer (CRPC) metastatic to bone (the TAXIUM trial)

Abstract: Combined therapy with docetaxel and (186)Re-HEDP is generally well tolerated in patients with CRPC metastatic to bone. We will conduct a randomized phase II study using three cycles of docetaxel 75 mg/m(2) 3-weekly followed by (188)Re-HEDP 40 MBq/kg body weight, followed by another three cycles of docetaxel 75 mg/m(2), followed by (188)Re-HEDP 20 MBq/kg body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This observation may be consistent with the finding that the moderate accumulation of 188 Re-liposome in orthotopic lung cancer cells was not sufficient to cause tumor death but did suppress tumor growth. Several lines of evidence have shown that the combination of 188 Re and chemotherapy or multiple dosages of 188 Re may increase the cytotoxic response in various cancers (21,28,32). It would be advantageous to design different regimes to evaluate whether 188 Re-liposome treatment can eradicate NSCLC and reach maximum therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This observation may be consistent with the finding that the moderate accumulation of 188 Re-liposome in orthotopic lung cancer cells was not sufficient to cause tumor death but did suppress tumor growth. Several lines of evidence have shown that the combination of 188 Re and chemotherapy or multiple dosages of 188 Re may increase the cytotoxic response in various cancers (21,28,32). It would be advantageous to design different regimes to evaluate whether 188 Re-liposome treatment can eradicate NSCLC and reach maximum therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bone marrow suppression and the subsequent adverse effects could be affected by various factors other than the dose administered. Suggested factors include the patient's overall condition, metastatic load, pretreatment blood cell count, and previous therapies (28,29). Our study showed that declines in blood cell count do not depend solely on the dose administered and that baseline complete blood count is important when selecting the best treatment.…”
Section: Discussionmentioning
confidence: 79%
“…At absorbed doses that are equivalent to those of low-LET radiation, high-LET particles are more cytotoxic. This phenomenon is called “radiation quality.” Most of the radionuclides used in internal radiotherapy; such as iodine-131 (Grunwald and Ezziddin, 2010; Leahy and Turner, 2011), yttrium-90 (Kulik et al, 2008; Menda et al, 2010; Kunikowska et al, 2011), lutetium-177 (Gains et al, 2011; Kunikowska et al, 2011), 188 Re (Kumar et al, 2007; Torres-Garcia et al, 2008), or rhenium-186 (Syed et al, 2006; van Dodewaard-de Jong et al, 2011); emit low-LET radiation of 0.2 keV/μm in the form of β-particles as well as internal conversion electrons (Milenic et al, 2004). High-LET particle emitters used in internal radiotherapy only include the α-emitters bismuth-213, bismuth-212, and astatine-211, as well as lead-212 and actinium-225, which generate bismuth-212 and bismuth-213, respectively.…”
Section: Radionuclides For Nanovectorized Radiotherapymentioning
confidence: 99%